Women Empowerment Through Entrepreneurship - T. Lavanaya (New Century Publications (1 Jan 2010), 2010)
In the Indian context
Includes index
Includes bibliographical references (p. [189]-203)
Keywords: Businesswomen -- India; Entrepreneurship -- India; Women in economic development -- Government policy -- India; Women in economic development -- India